2022
DOI: 10.3389/fonc.2022.1064817
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A novel LHFPL3::NTRK2 fusion in dysembryoplastic neuroepithelial tumor

Abstract: Neurotrophic tyrosine receptor kinase (NTRK) rearrangements are oncogenic drivers of various types of adult and pediatric tumors, including gliomas. However, NTRK rearrangements are extremely rare in glioneuronal tumors. Here, we report a novel NTRK2 rearrangement in a 24-year-old female with dysembryoplastic neuroepithelial tumor (DNT), a circumscribed WHO grade I benign tumor associated with epilepsy. By utilizing targeted RNA next-generation sequencing (NGS), fluorescence in situ hybridization (FISH), rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A classic example of transcription factor fusion is the EWSR1::FLI1 fusion, which is a common driver in Ewing sarcoma [79,80]. The most notable protein kinases involved in fusions include the MAST kinases in breast cancer [81], present in 3 to 5% of cases, as well as RET in various cancers (particularly lung and thyroid) [76,[82][83][84] and other RTKs in a variety of tumors [36,36,[85][86][87][88][89][90][91][92][93][94][95][96][97]. Such rearrangements are occasionally cancer-specific, or may be observable in distinctly different cancer types.…”
Section: Protein-level Analysis Of Oncofusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A classic example of transcription factor fusion is the EWSR1::FLI1 fusion, which is a common driver in Ewing sarcoma [79,80]. The most notable protein kinases involved in fusions include the MAST kinases in breast cancer [81], present in 3 to 5% of cases, as well as RET in various cancers (particularly lung and thyroid) [76,[82][83][84] and other RTKs in a variety of tumors [36,36,[85][86][87][88][89][90][91][92][93][94][95][96][97]. Such rearrangements are occasionally cancer-specific, or may be observable in distinctly different cancer types.…”
Section: Protein-level Analysis Of Oncofusionsmentioning
confidence: 99%
“…The vast majority of fusions identified in MPS studies are non-recurring, and, as such, have been identified as stochastic events [19]. While large-scale MPS efforts have been enormously productive in identifying fusion break points, novel oncofusions and their acting mechanisms are still being identified from MPS data at an accelerating pace [85][86][87][88][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120], and while multiple fusion databases are available [64,121,122], a centralized and standardized hub akin to, for example, IntAct [123] for interaction data or UniProt [124] for protein information has yet to emerge.…”
Section: Protein-level Analysis Of Oncofusionsmentioning
confidence: 99%